Defensa fiscal. Aspectos procesales del juicio de amparo - Sevilla Lizcano, Adrián Gilberto (Universidad Michoacana de San Nicolas de Hidalgo, 2024)
Tax defense involves knowing the general legal requirements of tax acts and resolutions, the rules of the Administrative Execution Procedure and the Contentious Administrative Trial; as well as the ordinary resources suitable to combat tax acts and resolutions contrary to legality. In the case of indirect protection, it was established that the cases in which it contributes to the tax defense strategy are the following: before the payment of an Unconstitutional tax; withholding of an unconstitutional tax; notification of an act of tax authority based on a Law that is considered unconstitutional; and, acts executed in the processing of a trial before the Federal Court of Fiscal and Administrative Justice that has an execution on people or things that is impossible to repair. In direct protection in tax matters, in the case of violations of guarantees or human rights committed in the final sentences handed down to the Contentious Administrative Trial, the cases in which it is effective are: when these sentences are contrary to the letter of the law applicable to the case; contrary to the legal interpretation of the law; to general principles of law in the absence of applicable law; when they include persons, actions or exceptions that have not been the subject of the contentious administrative trial (plus petitio); When they do not understand all the things that were the subject of the trial, that is to say to all people actions or exceptions either by omission or express denial (infra petitio); or, when they are based on a rule that is contrary to the principles of constitutional validity of taxes of proportionality and equity, tax legality or legal reservation.

La defensa fiscal implica conocer los requisitos legales generales de los actos y resoluciones fiscales, las reglas del Procedimiento Administrativo de Ejecución y el Juicio Contencioso Administrativo; así como, de los recursos ordinarios idóneos para combatir los actos y resoluciones fiscales contrarios a la legalidad. En el caso del amparo indirecto, quedó establecido que los casos en que abona a la estrategia de defensa fiscal son los siguientes: ante el pago de un impuesto Inconstitucional; retención de un impuesto inconstitucional; notificación de un acto de autoridad impositiva fundado en una Ley que se considera inconstitucional; y, actos ejecutados en la tramitación de un juicio ante el Tribunal Federal de Justicia Fiscal y Administrativa que tenga sobre las personas o las cosas una ejecución que sea de imposible reparación. En amparo directo en materia fiscal, tratándose de violaciones a garantías o derechos humanos cometidas en las sentencias definitivas recaídas al Juicio Contencioso Administrativo los casos en que es eficaz son: cuando esas sentencias sean contrarias a la letra de la ley aplicable al caso; contrarias a la interpretación jurídica de la ley; a los principios generales de derecho a falta de ley aplicable; cuando comprendan a personas, acciones o excepciones que no hayan sido objeto del juicio contencioso administrativo (plus petitio); cuando no comprendan todas las cosas que fueron objeto del juicio es decir a todas las personas acciones o excepciones ya sea por omisión o negación expresa (infra petitio); o, cuando se sustenten en una norma que resulte contraria a los principios de validez constitucional de los impuestos de proporcionalidad y equidad, al de legalidad tributaria o al de reserva de ley.
Facultad de Contaduría y Ciencias Administrativas. Maestría en Fiscal
Keywords: info:eu-repo/classification/cti/5; FCCA-M-2024-1030; Fiscal; Amparo; Inconstitucionalidad; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/18840